(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
This project demonstrates the feasibility of creating a theme park on Ecuadorian chocolate in the canton of Naranjal, which aims to strengthen and improve the tourism of the canton and its surroundings, through a novel establishment and family entertainment. The idea was born from the importance of products such as cocoa and chocolate in the economy of Ecuador and the need for a new place that offers integration and entertainment to the public, both national and foreign. Each chapter is part of an extensive research and planning process, such as a correct market study, where the acceptance of the project by the public and private sectors was known, a marketing plan detailing strategies for each element of the marketing mix, an organizational analysis of what will lead the company to be formed and the respective engineering of the same, showing the different areas that will make up the Chocolate Theme Park. In addition, the financial analysis is included, where investment values, income and projected cash flows are indicated to demonstrate the viability of the project.